Buckypaper / TiO2 composite material, sol-gel preparation method thereof and application of Buckypaper / TiO2 composite material in photocatalytic degradation

The Bucky paper/TiO2 composite material prepared by the sol-gel method uses the synergistic effect of Ti-O-C covalent bond and carbon nanotubes to solve the problem of TiO2 powder recovery and the problem of low efficiency of traditional supporting substrates, achieving high-efficiency photocatalysis Degradation and environmentally friendly catalyst recovery.

CN119140082APending Publication Date: 2024-12-17SHENYANG LIGONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411039190.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing TiO2 powder is difficult to recover after photocatalytic reaction, resulting in secondary contamination, and the traditional support substrate is not ideal for photocatalytic efficiency.

Method used

The sol-gel method is used to prepare the Bucky paper/TiO2 composite material, and Ti-O-C covalent bond is formed on the Bucky paper by uniformly distributing TiO2, and combined with carbon nanotubes to improve the photocatalytic efficiency and realize the recycling of the catalyst.

Benefits of technology

The photocatalytic degradation efficiency is improved to 99.34%, and secondary pollution is avoided. The material has good flexibility and mechanical properties, and can effectively recover used catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140082A_ABST
    Figure CN119140082A_ABST
Patent Text Reader

Abstract

The invention discloses a Bucky paper / TiO2 composite material, a sol-gel preparation method thereof and application of the Bucky paper / TiO2 composite material in photocatalytic degradation, and belongs to the technical field of photocatalysis. The Bucky paper / TiO2 composite material comprises Bucky paper and anatase type TiO2 uniformly distributed on the Bucky paper, and a Ti-O-C covalent bond is formed. The preparation method comprises the following steps: firstly, preparing TiO2 sol, mixing the TiO2 sol with the Bucky paper, drying, preserving heat, and cooling to obtain the Bucky paper / TiO2 composite material. According to the photocatalytic degradation performance of the Bucky paper / TiO2 composite material under ultraviolet light, the highest photocatalytic degradation efficiency can reach 99.34%. According to the present invention, the CNTs are used as the raw material, the paper-shaped structure Bucky paper composed of the CNTs has good flexibility and good convenience, the advantages of the CNTs are maintained, the CNTs are compounded with the TiO2, such that the photocatalytic efficiency can be improved, the used Bucky paper / TiO2 can be recycled, and the secondary pollution is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photocatalysis technology, and specifically relates to buckypaper / TiO 2 Composite materials and their sol-gel preparation and application in photocatalytic degradation. Background Art

[0002] The rapid development of industrial society has brought convenience to mankind, but also brought many problems. Dyes, toxic solvents, pesticides and other organic pollutants discharged into the environment have caused considerable pollution to water bodies and seriously endangered human health. The use of photocatalytic technology to treat water pollution has the advantages of high degradation efficiency, mild reaction conditions and low energy consumption, and has a good development prospect.

[0003] TiO 2 It has been widely studied due to its chemical stability, non-toxicity and low cost. 2 The disadvantage of powder is that it is difficult to recover the catalyst from water after the photocatalytic reaction, which will cause secondary pollution. One way to solve this problem is to convert TiO 2 Loaded on a large-area substrate. Some materials have been used as supporting substrates for titanium dioxide, such as optical fiber, glass, and silicon wafers. These substrates do not contribute to the photocatalytic process and may even reduce the photocatalytic efficiency, so the photocatalytic effect is not ideal. New nanocarbon materials have become a research hotspot for scholars in the field of photocatalysis due to their advantages such as high conductivity and large specific surface area. Combining nanocarbon materials with semiconductor photocatalysts is one of the many research directions for composite modification of photocatalysts. The large specific surface area of ​​carbon materials can not only provide more reactive active sites and enhance the adsorption performance of the material, but also promote the separation of photogenerated carriers and significantly inhibit electron-hole recombination. Carbon nanotubes (CNTs) are a type of carbon nanomaterial. Combining CNTs and TiO 2 The prepared composite material showed a synergistic effect, and the photocatalytic efficiency was significantly better than that of single TiO 2 and CNTs. However, discrete TiO 2 / CNTs and TiO 2 There is also the problem of difficulty in recycling. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a buckypaper / TiO 2 Composite materials and their sol-gel preparation and application in photocatalytic degradation. Buckypaper / TiO 2 Composite materials, prepared buckypaper / TiO 2The composite material showed a synergistic effect, effectively promoted the separation of charge carriers, and further improved the photocatalytic efficiency. Taking methyl orange solution as the target degradation product, the buckypaper / TiO 2 The photocatalytic degradation performance of the composite material under ultraviolet light can reach a maximum photocatalytic degradation efficiency of 99.34%. The paper-like structure of buckypaper composed of CNTs has good flexibility and convenience, maintaining the advantages of carbon nanotubes and combining it with TiO 2 Composite, not only can improve the photocatalytic efficiency, but also can be used for the used buckypaper / TiO 2 Recycling can avoid secondary pollution.

[0005] In order to achieve the above object, the present invention adopts the following scheme:

[0006] Buckypaper / TiO 2 Composite material, including buckypaper and anatase TiO uniformly distributed on buckypaper 2 , and form a Ti-OC covalent bond.

[0007] The buckypaper / TiO 2 The composite material is used in photocatalytic degradation as a photocatalyst to degrade organic pollutants in water. Under ultraviolet light, the photocatalytic degradation efficiency can reach more than 99%.

[0008] Buckypaper / TiO 2 The sol-gel preparation method of the composite material comprises the following steps:

[0009] S1: Configuration of TiO 2 Reaction Sol

[0010] (1) Ethanol-water mixed solution: by volume ratio, anhydrous ethanol: acidic deionized water = (12-13): (17-18), to obtain a mixed solution A;

[0011] (2) In molar ratio, tetrabutyl titanate: acetylacetone = 1: (0.70-0.71); weigh the raw materials, add the mixed solution of tetrabutyl titanate and acetylacetone into anhydrous ethanol while stirring, mix well, and form a mixed solution B; wherein, in terms of solid-liquid ratio, the mixed solution of tetrabutyl titanate and acetylacetone: anhydrous ethanol = (410-411) g: (250-260) mL;

[0012] In (1) of S1, the acidic deionized water is deionized water adjusted with nitric acid to a pH of 3.

[0013] (3) Mixing the mixed solution A and the mixed solution B uniformly with stirring to obtain a uniform and transparent sol; and then adjusting the volume to obtain 0.5 to 1 mol / L TiO 2Sol; Static aging for more than 24 hours to obtain aged TiO 2 Sol;

[0014] S2: Preparation of Buckypaper / TiO 2 Composite Materials

[0015] The aged TiO 2 The sol was spin-coated on the buckypaper, dried, kept warm, and cooled in the furnace to obtain buckypaper / TiO 2 Composite materials.

[0016] In the S2, the thickness of the buckypaper is 10-15 μm, the strength is 60-120 MPa, and the mass percentage of the metal is 5%.

[0017] In the above-mentioned S2, the drying temperature is 40-50° C. and the drying time is 1-2 hours.

[0018] In the S2, the insulation temperature is 400-500° C. and the insulation time is 2-3 hours.

[0019] Buckypaper / TiO 2 The composite material is prepared by adopting the preparation method.

[0020] The above steps are only for describing the technical solution more clearly, and are not intended to limit the order of the operation process. Some steps can be replaced before or after without affecting the final effect.

[0021] Buckypaper / TiO 2 The composite material and its sol-gel preparation method and its application in photocatalytic degradation have the following beneficial effects:

[0022] (1) The present invention uses a sol-gel method to prepare buckypaper / TiO 2 Composite materials, the preparation materials are harmless to the human body and do not pollute the environment; the preparation process is simple and the cost is low.

[0023] (2) Under the irradiation of external light, electrons move from TiO 2 The valence band of the TiO2 is excited to the conduction band, leaving holes in the valence band. The carbon nanotubes in buckypaper are not only a supporting material, but also a material with a bandgap wider than TiO2. 2 Therefore, electrons migrate to the conduction band of carbon nanotubes at the same time. 2 O acts as an electron donor, O 2 As an electron acceptor, hydroxyl radicals and superoxide radicals are formed. These generated free radicals can decompose pollutants into H 2 O、CO 2 And other non-toxic and harmless substances, thereby effectively degrading other dyes, especially methyl orange.

[0024] (3) Using the preparation method of the present invention, TiO 2 Loading on buckypaper can not only effectively solve the problem of single TiO 2 The problem of easy agglomeration can also be solved by increasing the specific surface area of ​​the catalyst and improving the adsorption capacity of pollutants. 2 The Ti-OC bonding can promote the separation of charge carriers, thereby improving the photocatalytic efficiency. 2 The composite material can almost completely degrade methyl orange within 90 minutes.

[0025] (4)TiO 2 、TiO 2 / CNTs are all powdery structures and cannot be recycled after being put into water. Buckypaper is a self-supporting carbon nanotube paper with a non-woven structure formed by the entanglement of carbon nanotubes due to the van der Waals force. It has good flexibility, mechanical properties and conductivity. Buckypaper / TiO 2 The buckypaper in the composite material can be recycled to avoid secondary pollution as long as the paper structure is intact. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Buckypaper / TiO in Example 1 of the present invention 2 Sample and Comparative Example 1TiO 2 XRD pattern of .

[0027] Figure 2 Buckypaper / TiO in Example 1-2 of the present invention 2 Composite materials and comparative examples 2-3 Buckypaper / TiO 2 Composite material and comparative example 1TiO 2 SEM images of .

[0028] Figure 3 Buckypaper / TiO in Example 1 of the present invention 2 XPS graph of the composite material.

[0029] Figure 4 Buckypaper / TiO in Example 1-2 of the present invention 2 Composite materials and comparative examples 2-3 Buckypaper / TiO 2 Composite material and comparative example 1TiO 2 Photocatalytic degradation curve and kinetic curve of sample degradation of MO aqueous solution. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with embodiments.

[0031] Buckypaper / TiO2 The sol-gel preparation method of the composite material comprises the following steps:

[0032] Step 1: Configure TiO 2 Reaction sol.

[0033] (1) Weigh the raw materials according to the ratio, add 100g of anhydrous ethanol to 180g of deionized water to prepare a mixed solution A.

[0034] (2) The raw materials were weighed according to the ratio, and 340.3 g of tetrabutyl titanate and 71 g of acetylacetone were slowly added into 200 g of anhydrous ethanol under rapid stirring to form a mixed solution B.

[0035] (3) Mixed solution A is slowly added to mixed solution B with a burette under rapid stirring to obtain a uniform and transparent sol; finally, the volume of the sol is supplemented to 1 L with anhydrous ethanol to obtain 1 mol / L TiO 2 The obtained sol is aged for 24 hours before use.

[0036] Step 2: Preparation of Buckypaper / TiO 2 Composite materials.

[0037] The prepared TiO 2 The sol was diluted to 0.1mol / L, 0.25mol / L, 0.5mol / L, and then 10ml of each sol was taken. The buckypaper was coated with the sol using a sol spin coater, dried in a drying oven, and then kept warm in a vacuum furnace. The samples were marked as R0.1, R0.25, R0.5, and R1.0. At the same time, 1mol / L of TiO 2 10 ml was reacted under the same conditions.

[0038] Example 1

[0039] Buckypaper / TiO 2 The sol-gel preparation method of the composite material comprises the following steps:

[0040] Step 1: Configure TiO 2 Reaction sol.

[0041] (1) According to the ratio, weigh the raw materials and add 100 g of anhydrous ethanol into 180 g of deionized water adjusted to pH 3 with nitric acid to prepare a mixed solution A.

[0042] (2) The raw materials were weighed according to the ratio, and 340.3 g of tetrabutyl titanate and 71 g of acetylacetone were first mixed, and the resulting mixed solution was slowly added to 200 g of anhydrous ethanol under rapid stirring to form a mixed solution B.

[0043] (3) Mixed solution A is slowly added to mixed solution B with a burette under rapid stirring to obtain a uniform and transparent sol; finally, the volume of the sol is supplemented to 1 L with anhydrous ethanol to obtain 1 mol / L TiO 2 The obtained sol is aged for 24 hours before use.

[0044] Step 2: Preparation of Buckypaper / TiO 2 Composite materials.

[0045] The prepared 1 mol / L TiO 2 Take 10 mL of the sol, coat the buckypaper with the sol using a sol spin coater, dry it in a drying oven at 40°C for 1 h, and keep it in a vacuum oven at 450°C for 2 h.

[0046] Step 3, photocatalytic experiment.

[0047] The photocatalytic degradation experiment was carried out using methyl orange (MO) under ultraviolet light (500W high pressure mercury lamp) at a distance of 25 cm above the beaker. 2 Composite material or 10 mg TiO 2 (Comparative Example) was placed in a glass container containing 100 ml of MO aqueous solution (10 mg / L). Before light irradiation, the mixture of the solution and the sample was magnetically stirred in the dark for 30 min to achieve adsorption-desorption equilibrium between the composite material and methyl orange (MO). Then, 4 ml of the supernatant was taken every 10 min during the irradiation period, and the residual concentration of MO was determined using a UV-visible spectrophotometer.

[0048] Buckypaper / TiO prepared in this example 2 The composite material is R1.0.

[0049] Comparative Example 2

[0050] Buckypaper / TiO 2 The preparation method of the composite material is the same as that of Example 1, except that the TiO 2 The concentration of the sol was 0.25 mol / mL.

[0051] Buckypaper / TiO prepared in this comparative example 2 The composite material is R0.25.

[0052] Example 2

[0053] Buckypaper / TiO 2 The preparation method of the composite material is the same as that of Example 1, except that the TiO 2 The concentration of the sol was 0.5 mol / mL.

[0054] Buckypaper / TiO prepared in this example2 The composite material is R0.5.

[0055] Comparative Example 3

[0056] Buckypaper / TiO 2 The preparation method of the composite material is the same as that of Example 1, except that the TiO 2 The concentration of the sol was 0.1 mol / mL.

[0057] Buckypaper / TiO prepared in this comparative example 2 The composite material is R0.1.

[0058] Comparative Example 1

[0059] Step 1: Take 1 mol / L TiO 2 10 ml was reacted under the same conditions.

[0060] Analysis test case

[0061] Buckypaper / TiO prepared in Example 1 2 The composite materials were subjected to XRD analysis. Figure 1 The diffraction peaks at 2θ=26.06° and 2θ=44.56° correspond to the (002) and (100) crystal planes of buckypaper. 2 The standard PDF card (No.21-1272) shows that the prepared TiO 2 It is anatase type, and the diffraction peaks at 2θ = 25.3°, 2θ = 37.9°, 2θ = 47.9°, 2θ = 54.7°, 2θ = 62.8°, 2θ = 69.6°, and 2θ = 75.3° correspond to anatase TiO 2 The (101), (004), (200), (211), (204), (220), and (215) crystal planes have good crystallinity. In the XRD pattern of R1.0, it is observed that TiO 2 The diffraction peak corresponding to the (101) crystal plane coincides with the (002) diffraction peak of the buckypaper, and the diffraction peak of the composite material at 2θ = 54.7° corresponds to anatase TiO 2 The diffraction peak at 2θ = 44.56° corresponds to the (100) crystal plane of buckypaper, which is not matched to the (211) crystal plane of TiO in the R1.0 composite material. 2 The other characteristic peaks may be due to the TiO 2 The amount is small, and the value is smaller than that of carbon nanotubes in buckypaper, which is not detected by the instrument. It may also be because the TiO2 combined with buckypaper 2 The crystallinity is not good enough.

[0062] Buckypaper / TiO 2 Composite material and comparative example 1TiO 2 See SEM pictures Figure 2 It can be observed from the figure that compared with the carbon nanotubes in the buckypaper, the carbon nanotubes in the composite material sample are obviously thicker, and the surface of the carbon nanotubes is coated with a thick layer of TiO 2 , and with the increase of sol concentration, the TiO 2 The amount of TiO coated on buckypaper 2 Although it is similar to a whole attached to the surface of the carbon nanotube, it is only on a single carbon nanotube, and there is no agglomerated TiO between the carbon nanotubes. 2 Covering, such a structure will be beneficial to the transmission of electron-hole pairs and improve the photocatalytic activity.

[0063] Figure 3 is the XPS spectrum of the composite material. Figure 3 In (a), the peaks at 459.25 eV and 464.89 eV in sample R1.0 represent Ti 2P in anatase titanium dioxide. 3 / 2 and Ti 2P 1 / 2 , these signals are Ti 4+ The oxidation state of the samples indicates that anatase TiO 2 The C 1s spectrum is shown in 3(b) and can be divided into two peaks. The C1s peak at 284.5 eV is attributed to the sp 3 hybrid carbon, while the peak at 285.6 eV can be attributed to the C-O bond. These functional groups on the buckypaper contribute to the 2 The anchoring on the buckypaper surface helps to form Ti-OC covalent bonds. Figure 3 In (c), two peaks are observed at around 529.7 eV and 531.0 eV, corresponding to Ti-O-Ti and C=O bonds, respectively. In the R1.0 sample, a peak appears at about 532.1 eV, which is attributed to the Ti-OC bond. The samples synthesized by the sol-gel method at 450 °C show different characteristics: TiO 2 The Ti-OC bonds form a stable chemical connection with the carbon nanotubes. The formation of these chemical bonds promotes electron transfer, which significantly improves the photocatalytic performance of the material.

[0064] Buckypaper / TiO prepared in Example 1 2 Composite materials and comparative example 1TiO 2 The degradation rate and first-order kinetic curve of Figure 4 , R0.1, R0.25, R0.5, R1.0 and TiO 2The photocatalytic degradation rates of the samples were 80.6%, 76.84%, 99.01%, 99.34% and 85.22% respectively. The photocatalytic efficiency of the R1.0 sample was the highest and the photocatalytic effect was the best. Buckypaper / TiO prepared by sol-gel method 2 The composite material has a maximum catalytic efficiency of 99.34% within 90 minutes, and a degradation rate constant of 0.0495 minutes. -1 .

[0065] Comparative Example 4

[0066] In the preparation of the ethanol-water mixed solution, neutral deionized water is used. The other conditions are the same as those in Example 1. However, if nitric acid is not added, the violent hydrolysis of tetrabutyl titanate cannot be suppressed. Too fast hydrolysis of tetrabutyl titanate will form larger particles, thereby making the sol turbid.

[0067] Comparative Example 5

[0068] The hydrothermal method was used to prepare TiO 2 The raw materials and buckypaper were mixed and kept at 150℃ for 3 to 9 hours to obtain buckypaper / TiO 2 The photocatalytic degradation rate of the composite material is lower than that of buckypaper / TiO prepared by sol-gel method. 2 The photocatalytic degradation rate of the composite material is due to the fact that the composite material prepared by the sol-gel method has a 2 A stable Ti-OC bond is formed between the carbon nanotubes, which helps to reduce the recombination of electron-hole pairs and thus significantly improve the photocatalytic efficiency.

Claims

1. A buckypaper / TiO2 composite material, characterized in that: It includes buckypaper and rutile TiO2 uniformly distributed on the buckypaper, and forms a Ti-OC covalent bond.

2. The sol-gel preparation method of the buckypaper / TiO2 composite material according to claim 1, characterized in that: The following steps are involved: S1: Preparation of TiO2 reaction sol (1) Ethanol-water mixed solution: Anhydrous ethanol and acidic deionized water are mixed to obtain a mixed solution A; (2) weighing raw materials, adding a mixed solution of tetrabutyl titanate and acetylacetone into anhydrous ethanol while stirring, and mixing them evenly to form a mixed solution B; (3) Mixing the mixed solution A and the mixed solution B uniformly with stirring to obtain a uniform and transparent sol; and fixing the volume to obtain a 0.5-1 mol / L TiO2 sol; and aging the mixture for more than 24 hours to obtain an aged TiO2 sol; S2: Preparation of Buckypaper / TiO2 Composites The aged TiO2 sol is spin-coated on the buckypaper, dried, kept warm, and cooled in a furnace to obtain a buckypaper / TiO2 composite material.

3. The sol-gel preparation method of the buckypaper / TiO2 composite material according to claim 2, characterized in that: In (1) of S1, the volume ratio of anhydrous ethanol: acidic deionized water is (12-13): (17-18).

4. The sol-gel preparation method of the buckypaper / TiO2 composite material according to claim 2, characterized in that: In (1) of S1, the acidic deionized water is deionized water with a pH of 3.

5. The sol-gel preparation method of the buckypaper / TiO2 composite material according to claim 2, characterized in that: In (2) of S1, in molar ratio, tetrabutyl titanate: acetylacetone = 1: (0.70-0.71); and / or, in solid-liquid ratio, a mixture of tetrabutyl titanate and acetylacetone: anhydrous ethanol = (410-411) g: (250-260) mL.

6. The sol-gel preparation method of the buckypaper / TiO2 composite material according to claim 2, characterized in that: In the S2, the thickness of the buckypaper is 10-15 μm, the strength is 60-120 MPa, and the mass percentage of the metal is 5%.

7. The sol-gel preparation method of the buckypaper / TiO2 composite material according to claim 2, characterized in that: In the above-mentioned S2, the drying temperature is 40-50° C. and the drying time is 1-2 hours.

8. The sol-gel preparation method of the buckypaper / TiO2 composite material according to claim 2, characterized in that: In the S2, the insulation temperature is 400-500° C. and the insulation time is 2-3 hours.

9. Application of a buckypaper / TiO2 composite material in photocatalytic degradation, characterized in that: The buckypaper / TiO2 composite material described in claim 1 or the buckypaper / TiO2 composite material prepared by the preparation method of any one of claims 2-8 is used as a photocatalyst to degrade organic pollutants in water.

10. The use of the buckypaper / TiO2 composite material in photocatalytic degradation according to claim 9, characterized in that: The organic pollutant in the water is methyl orange. Under ultraviolet light, the photocatalytic degradation efficiency of the buckypaper / TiO2 composite material reaches more than 99%.